2023
DOI: 10.1177/14791641231179878
|View full text |Cite
|
Sign up to set email alerts
|

Health care registers can be instrumental for endpoint capture in clinical diabetes trials: example of microvascular complications in Swedish patients with type 2 diabetes

Abstract: Aims SMARTEST is a register-based randomized clinical trial (RRCT) that compares dapagliflozin to metformin in early-stage type 2 diabetes. The primary outcome includes progression of microvascular complications based on data from the Swedish National Diabetes Register (NDR). In this sub-study, the aim was to validate microvascular complication variables in the NDR against electronic health records (EHRs). Methods Data were extracted from EHRs of 276 SMARTEST participants with a median observation period of 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Data reported to NDR includes risk factors associated with long-term diabetes complications such as level of glycated haemoglobin (HbA1c), systolic blood pressure (SBP), lipid profile, diabetes duration, type of glucose-lowering treatment, type of diabetes, presence and severity of DR and nephropathy. Recently, DR status was validated as an endpoint capture in the NDR with excellent agreement between the registry and electronic health records (Lundqvist et al, 2023). The wide span of reported variables in the registry allows for in-depth analyses, in turn facilitating the description of trends and changes in prevalence and the description of DR incidence and factors known to be associated with DR. Over the study period, NDR reported an average yearly coverage of 84.6% of all PwD in Sweden (Nationella Diabetesregistret, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Data reported to NDR includes risk factors associated with long-term diabetes complications such as level of glycated haemoglobin (HbA1c), systolic blood pressure (SBP), lipid profile, diabetes duration, type of glucose-lowering treatment, type of diabetes, presence and severity of DR and nephropathy. Recently, DR status was validated as an endpoint capture in the NDR with excellent agreement between the registry and electronic health records (Lundqvist et al, 2023). The wide span of reported variables in the registry allows for in-depth analyses, in turn facilitating the description of trends and changes in prevalence and the description of DR incidence and factors known to be associated with DR. Over the study period, NDR reported an average yearly coverage of 84.6% of all PwD in Sweden (Nationella Diabetesregistret, 2017).…”
Section: Discussionmentioning
confidence: 99%